2022
DOI: 10.1180/mgm.2022.138
|View full text |Cite
|
Sign up to set email alerts
|

Argentotetrahedrite-(Cd), Ag6(Cu4Cd2)Sb4S13, a new member of the tetrahedrite group from Rudno nad Hronom, Slovakia.

Abstract: Argentotetrahedrite-(Cd), Ag6(Cu4Cd2)Sb4S13, has been approved as a new mineral species by the International Mineralogical Association -Commission on New Minerals, Nomenclature and Classification (IMA-CNMNC) using samples from Rudno nad Hronom, Slovak Republic. It occurs as anhedral grains up to 30 μm in size, steel-grey to black in colour, with a metallic lustre, in association with greenockite and other tetrahedrite group minerals (argentotetrahedrite-(Zn), tetrahedrite-(Zn)), earlier base metal minerals, Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The tetrahedrally coordinated M(1) site has an average Me-S distance of 2.391 Å (Table 6), longer than that observed in mixed (Cu,Zn,Fe) tetrahedrally coordinated sites in tetrahedrite-group minerals (e.g. 2.342 Å - Wuensch, 1964;2.337 Å -Wuensch et al, 1966) and comparable to those observed in tennantite-(Cd) (2.370 Å - Biagioni et al, 2022a) and in argentotetrahedrite-(Cd) (2.38 Å - Mikuš et al, 2023). On the basis of the electron microprobe data, the occu- ).…”
Section: Crystal Structure Descriptionmentioning
confidence: 56%
See 3 more Smart Citations
“…The tetrahedrally coordinated M(1) site has an average Me-S distance of 2.391 Å (Table 6), longer than that observed in mixed (Cu,Zn,Fe) tetrahedrally coordinated sites in tetrahedrite-group minerals (e.g. 2.342 Å - Wuensch, 1964;2.337 Å -Wuensch et al, 1966) and comparable to those observed in tennantite-(Cd) (2.370 Å - Biagioni et al, 2022a) and in argentotetrahedrite-(Cd) (2.38 Å - Mikuš et al, 2023). On the basis of the electron microprobe data, the occu- ).…”
Section: Crystal Structure Descriptionmentioning
confidence: 56%
“…In addition to tetrahedrite-(Cd), two other species are represented by the As-isotype tennantite-(Cd) and the Ag-isotype argentotetrahedrite-(Cd). The former was described from the Cd-rich hydrothermal veins of the Berenguela district, Bolivia (Biagioni et al, 2022a), whereas the latter is a very recent addition to the freibergite series and was reported from the Au-Ag epithermal deposits of Rudno nad Hronom, Slovakia (Mikuš et al, 2023). Finally, the selenide hakite-(Cd) was reported from Příbram, central Bohemia, Czech Republic (Škácha et al, 2016Sejkora et al, 2022).…”
Section: Cadmium In Tetrahedrite-group Mineralsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modulated crystal structure can be rationalized and compared to other chemically related phases in the bismuth-sulfide system. The new mineral, zipserite, and its symbol zps were approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (IMA2022-075, Majzlan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%